Some Physico-chemical Properties of Mahonia acquifolium Fruits - Marakoglu, Tamer; Akbulut, Mehmet; Calisir, Sedat (Asian Journal of Chemistry, 2010)
Mahonia aquifolium fruits were investigated for some technological and chemical properties such as: dimensions, geometric mean diameter, sphericity, bulk density, fruit density, volume, terminal velocity, rupture strength, porosity, moisture, reducing sugar, total anthocyanin and phen-olics, crude protein, crude oil, crude energy, crude fiber, ash, pH, acidity, alcohol soluble extract and color. Mineral content of Mahonia aquifolium fruits growing in Turkey were established by Inductively Coupled Plasma Atomic Emission Spectrometer (ICP-AES). Mahonia aquifolium fruit contained high amounts of K, P, Ca, Na and Mg. The average pulp mass ratio, thickness, width, length, mass, volume, geometric mean diameter, sphericity and projected area were measured to be 88.21 %, 7.05 mm, 7.85 mm, 9.10 mm, 0.28 g, 233 mm3, 7.92 mm, 0.88 and 68.40 mm2, respectively. The energy, reducing sugar, protein, cellulose, oil, ash, acidity, total phenolics, total anthocyanin and soluble solid matter values of Mahonia aquifolium fruits were determined to be 47.85 kcal/100g, 47.6 g/kg, 30.8 g/kg, 17.8 g/kg, 21.7 g/kg, 11.0 g/kg, 33.7 g/kg, 4574.6 mg/kg, 655.64 mg/kg and 176.0 g/kg, respectively. It is very important to evaluate the technological properties of equipment used harvesting, transportation, storage and processing of fresh fruits. In additon, the information supplied on the chemical properties of the Mahonia aquifolium fruits serves as food in human nutrition.